THE USE OF SOCIAL INTERACTIVE WRITING FOR ENGLISH LANGUAGE LEARNERS (SWELL) METHOD TO DEVELOP THE STUDENTSâ ABILITY TO WRITE NARRATIVE TEXT - Asriati AM, St. (Lembaga Perpustakaan Unismuh Makassar, 2013)
This research aimed to find out the development of the studentsâ ability to write narrative text viewed from both generic structure and language use at XI IPA of SMA Muhammadiyah Sungguminasa, Gowa. The type of this research was a Classroom Action Research consisted of two cycles. One cycle consisted of four meetings. Thus, that there were eight meetings for two cycles. This classroom action research was done at XI IPA of SMA Muhammadiyah Sungguminasa, Gowa. The research subjects were the students of class XI in 2012/2013 academic year with 26 students. Those consisted of 10 men and 16 women. The instruments of this research were writing test and observation. The research findings indicated that the Use of SWELL Method could develop the studentsâ ability to write narrative text viewed from generic structure and language use. It was proved by the studentsâ mean score in cycle 2 test result was (77.81) which developed 16.31 % from the cycle 1 mean score (66.98). It was highly developed from diagnostic test (D â test) mean score (58.69). The studentsâ development in cycle 2 indicated that it had met the researcher score target (75), and considered to be successful criteria in developing the studentsâ ability to write narrative text covering generic structure and language use.Keywords: writing, development, social interactive writingPenelitian ini bertujuan untuk mengetahui perkembangan kemampuan siswa untuk menulis teks naratif dilihat dari kedua struktur generik dan menggunakan bahasa di XI IPA SMA Muhammadiyah Sungguminasa, Gowa. Jenis penelitian ini adalah Penelitian Tindakan Kelas terdiri dari dua siklus. Satu siklus terdiri dari empat pertemuan. Dengan demikian, bahwa ada delapan pertemuan selama dua siklus. Penelitian tindakan kelas ini dilakukan di XI IPA SMA Muhammadiyah Sungguminasa, Gowa. Subyek penelitian adalah siswa di kelas XI tahun akademik 2012/2013 dengan 26 siswa. Mereka terdiri dari 10 laki-laki dan 16 perempuan. Instrumen penelitian ini menulis tes dan observasi. Temuan penelitian menunjukkan bahwa Penggunaan Metode SWELL bisa mengembangkan kemampuan siswa untuk menulis teks naratif dilihat dari struktur generik dan penggunaan bahasa. Hal itu dibuktikan dengan nilai rata-rata siswa dalam hasil tes siklus 2 adalah (77,81) yang dikembangkan 16,31% dari siklus 1 berarti nilai (66,98). Itu sangat maju dari tes diagnostik (D - test) berarti skor (58,69). Siswa pembangunan di siklus 2 menunjukkan bahwa mereka telah mencapai target skor peneliti (75), dan dianggap sebagai kriteria sukses dalam mengembangkan siswa kemampuan untuk menulis teks naratif meliputi struktur generik dan penggunaan bahasa.Kata Kunci: menulis, pengembangan, menulis interaktif social.